2015
DOI: 10.3389/fpsyg.2015.00725
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive effects of fear and sadness induction on anger and aggressive behavior

Abstract: A recent study has reported that the successful implementation of cognitive regulation of emotion depends on higher-level cognitive functions, such as top-down control, which may be impaired in stressful situations. This calls for “cognition free” self-regulatory strategies that do not require top-down control. In contrast to the cognitive regulation of emotion that emphasizes the role of cognition, traditional Chinese philosophy and medicine views the relationship among different types of emotions as promotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 57 publications
(69 reference statements)
9
37
0
Order By: Relevance
“…Rather, this strategy implies two major points: First, it proposes that sadness is a potentially efficient emotion to counteract previously evoked anger and aggressive behavior; second, if sadness can be evoked in a harmless and effortless way (e.g., by watching sad movies), then it might be an alternative approach (relative to cognitive reappraisal) to regulate anger. Our recent study provided behavioral evidence supporting the hypothesis that SCA and found that subsequently induced sadness reduced an angry individual’s aggressive behavior (but not angry feelings) more than neutral or fear emotions ( Zhan et al, 2015 ). In that study, participants were first provoked by reading negative feedback on their viewpoints or by watching anger-inducing movie clips.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…Rather, this strategy implies two major points: First, it proposes that sadness is a potentially efficient emotion to counteract previously evoked anger and aggressive behavior; second, if sadness can be evoked in a harmless and effortless way (e.g., by watching sad movies), then it might be an alternative approach (relative to cognitive reappraisal) to regulate anger. Our recent study provided behavioral evidence supporting the hypothesis that SCA and found that subsequently induced sadness reduced an angry individual’s aggressive behavior (but not angry feelings) more than neutral or fear emotions ( Zhan et al, 2015 ). In that study, participants were first provoked by reading negative feedback on their viewpoints or by watching anger-inducing movie clips.…”
Section: Introductionsupporting
confidence: 60%
“…First, a previous study found that cognitive reappraisal fails to regulate fear conditioning under stress ( Raio et al, 2013 ). Furthermore, regarding the effects of the SCA strategy, our previous research showed that inducing sadness among participants (relative to fear and neutral emotions) after they were provoked decreased their aggression ( Zhan et al, 2015 ). The present study successfully replicated previous studies and directly compared cognitive reappraisal with the SCA strategy after controlling for the object of regulation (i.e., anger and aggressive behavior) and the means of regulation (i.e., both cognitive reappraisal and the regulatory sadness emotion were induced by watching videos) across conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One way ANOVA was performed by considering acoustic cues with affect ratings. Two hypothesis was examined in [19] regarding the modulation of anger and aggressive behavior. Anger and aggressive behavior was counteracted by sadness whereas they are promoted by fear.…”
Section: Introduction and Related Workmentioning
confidence: 99%